Poesia são-tomense : geografias em dispersão - Bayer, Adriana Elisabete (2012)
The history of the islands of São Tome and Príncipe is the colonization of the archipelago, the construction of the nation, and the reformulation of the national project. In each of these stages, different diasporas and stories of resistance to colonial rule and to the authoritarianism in post-independence period were manifested. Literature, especially poetry - object of this thesis - records the representation of a social space, which marks of it show the historicity of the space itself and its inhabitants, revealing the features identities that stand out in the process. This thesis aims to verify that São Tomé poetry, in its different ways to express, the diasporas reveal the way of historical and geographical changes, due to the interrelationship between human groups and social spaces. The interaction specifications determines whether the social space should be described as a landscape or as a territory. The poetic corpus selected for analysis belongs to the poets Francisco José Tenreiro, Caetano Costa Alegre, Tomás Medeiros, Fernando de Macedo; and to the poetesses Alda Espírito Santo, Olinda Beja, Conceição Lima. The theoretical background is found in different areas of knowledge, besides the poetry, the cultural geography, history, anthropology and social sciences.